Distributed remote sensing for naval undersea warfare : abbreviated version (National Academies Press, 2007)
The widespread availability of quiet, diesel electric submarines and inexpensive mines is posing a growing threat to global access by the U.S. Navy. In response, the Navy has expanded its undersea warfare efforts and put particular emphasis on the potential for new distributed remote sensing (DRS) approaches. To assist with this effort, the former Chief of Naval Operations requested the NRC to conduct an assessment of DRS for naval undersea warfare. This report provides a clear, near-term path by which useful DRS systems can be applied rapidly to pressing naval USW problems, and by which ongoing science and technology efforts can be directed toward the most useful options. The report contains information as described in 5 U.S.C. 552(b) and therefore could not be released to the public in its entirety. The public version consists of the front matter and executive summary.